Songs of Humpback whales (Megaptera novaeangliae): Described during winter mating season on a subarctic feeding ground in northeast Iceland - Lim, Rangyn, 1985- (2014)
Humpback whale (Megaptera novaeangliae) songs were first described and characterized by Payne and McVay in 1971. The elaborate vocal display of song is still not fully understood, but it likely represents an important behaviour in mating and sexual selection. Humpback whales are a migratory species known to produce long, stereotyped, complex songs in breeding grounds during the winter time. However, more studies are detecting songs outside of the usual tropical warm breeding areas, in migration routes as well as in higher-latitude feeding grounds. The study area, Skjálfandi Bay in northeast Iceland (66°07′N, 17°32′W), is an established high latitude feeding ground for humpback whales during the summer. Former cetacean acoustic monitoring studies from 2008 to 2009 in this location, indicated that humpback whale song vocalizations were present in multiple 1 minute recording sound files. The present study supports and markedly expands on the previous acoustic findings from this location. It demonstrates and describes extensive song occurrence in winter months that were not previously recorded. Long-term acoustic recordings were made in Skjálfandi Bay from 26 January – 12 March, 2011, using a bottom-moored Ecological Acoustic Recorder (EAR). The EAR was programmed to record in 10 minute cycles, every 5 minutes at a sampling rate of 16 kHz. The prevalence of songs by multiple individuals confirmed that at least part of the population remained in the productive waters throughout winter, and possibly year-round. The songs from this high latitude feeding ground also demonstrated a level of structure and pattern characteristic of songs described from mating grounds. The results had 19 phrase type classifications and displayed a predictable sequence from the cyclic patterns in the song recordings. Furthermore, peak song occurrence timing coincided with the peak timing of seasonal hormonal activity in sexually active humpback whales during breeding season in the Northern hemisphere. The findings demonstrate that this ...